Dyslipidemia and Superoxide Dismutase Activity in Children with Down Syndrome - Goyal, P; Singh, R; Yadav, A; Dutta, AK; Bhattacharjee, J (Journal of Nepal Paediatric Society, 2010)
Introduction: Down Syndrome (trisomy 21) provides an interesting natural model to study atherosclerosis, since these individuals appear to be protected from plaque formation. Methodology: We assessed the lipid levels, and superoxide dismutase (SOD) activity in 32 clinically diagnosed children of Down syndrome and 34 children matched for age and sex as controls. Results: SOD activity was found to be significantly higher (p=0.004) in children with Down Syndrome (mean=313.7 IU/ml) than in controls (mean140.2 IU/ ml). Significantly higher levels of serum triglyceride (154.7 mg/dl) and VLDL (33.9 mg/dl) were observed in Down Syndrome as compared to healthy controls (119.6 mg/dl and 23.9 mg/dl respectively; p<0.05 for each). However, the two groups did not show any significant difference in levels of serum HDL-C, LDL-C. Conclusion: The raised antioxidant activity of SOD, because of over expression of genes situated non chromosome 21, probably offers some protection against the development of atherosclerosis despite the occurrence of dyslipidemia. Key words: Chromosome 21; Down Syndrome; Trisomy 21; Superoxide dismutase. DOI: 10.3126/jnps.v30i3.3919 J Nep Paedtr Soc 2010;30(3):160-163